Protemblemaria perla, a new species of tube blenny (Perciformes: Chaenopsidae) from the tropical eastern Pacific - Hastings, Philip A. (2001)
Protemblemaria perla, from Isla del Rey, Islas Perlas, Panama, is distinctive in having a long unbranched cirrus on the posterior nostril, a U-shaped fleshy ridge bearing fleshy flaps and a pair of papillae on the nape, a relatively high number (18) of segmented dorsal-fin rays, and small rust-colored spots on the dorsal fin. Protemblemaria perla and P. punctata, from the southern Caribbean, share several morphological features and form a transisthmian species pair. Although the degree of color variation is unknown in P. perla, color varies greatly in P. bicirris and P. punctata, both of which have an orange morph.